QUALITY ANALYSIS OF PRACTICAL TRAINING IN VOCATIONAL AND TECHNICAL EDUCATION. CASE STUDY: ILFOV COUNTY, ROMANIA, ACADEMIC YEAR 2022-2023 - Florin Cristian CIOBĂNICĂ (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In an environment characterized by change and diversity in the labour market, vocational and technical education is undergoing a significant transformation. Vocational and technical educational institutions are obligated to adopt approaches that align with reality when faced with challenges in a social environment where employment opportunities and the demand for specialized workforce are diversified. This article presents the results of a qualitative research conducted at the pre-university education level in Ilfov County, based on the questionnaire that was administered to 502 students enrolled in educational institutions in Ilfov County, at the following specializations: Tourism and public food, Economics, Environmental Protection, Agriculture, Mechanics, Electronics and Automation, Construction, Installations, and Public Works. The purpose of this research was to understand how educational institutions, affected by industry regulations, adapt to the requirements of the labour market and the needs of direct beneficiaries. The present research utilized an indirect survey through a questionnaire, as the advantages of this opinion-sampling tool include allowing subjects to think thoroughly before responding, reducing the disruptive influence of the surveyor, and minimizing errors in data recording and interpretation. The questionnaire was addressed to students in vocational and technical education with the aim of determining to what extent the respondents are satisfied with the practical training courses completed in the 2022-2023 school year. Conclusions were drawn from the answers recorded on the entire sample which can later be translated into measures to improve the quality of internships.